THE DEVELOPMENT OF COMMUNICATIVE COMPETENCE IN FOREIGN LANGUAGES (Konferensiyalar | Conferences, 2024)
This scientific paper investigates the complex process of becoming a proficient communicator in another language. In addition to linguistic proficiency, communicative competence also includes sociolinguistic and strategic competencies. It is an essential component of language learning. The research explores the theoretical bases of communicative competence and looks at the potential applications for language learners and teachers. In addition, several elements that impact the growth of communicative competence are covered, including motivation, exposure to real language use, and cultural awareness. The paper also identifies successful teaching methods and tactics that can help foreign language learners become more proficient communicators. The objective of this study is to enhance comprehension of the process by which people can develop proficiency in a second language by illuminating these crucial elements.